(untitled) (Research, Society and Development, 2022)
A Basic Problematization Unit (UBP) is mainly a discursive memory flash that describes sociocultural practices. With its use, the teacher can provide different modes of interdisciplinary problematization and lead students to the practice of actions and reflections that can generate new knowledge. In this article, we review the theoretical foundations related to the UBP, highlighting its main characteristics and its structural freedom, followed by a review of the studies and academic productions based on the conception of the UBP. Likewise, we propose didactic guidelines that can help teachers in the planning and execution of UBPs as a concrete possibility for a conceptual approach to school contents that emerge from the book Geometry, which is part of the appendix of the Discourse on the Method, by René Descartes. At the end, we present some reflections that can help teachers in the use of this methodological proposal.